The body in museology as expression of identity in contemporary thought (Cadernos de Sociomuseologia, 2020)
In the present article we seek to reflect, within the scope of an PhD investigation in ULHT, Sociomuseology department, about tattoo as an artistic expression for cotemporary museology, where we try to give visibility to a process of identity, to a mapping of experiences and of affirmation of a territory that belongs to each one of us – our body. If on one hand, we seek to answer to one of the problems that we consider important in the today’s world, we also seek to reflect about some issues that concern the Museology and the Museums. Throughout this investigation we also seek, through fieldwork expressed by interviews with the tattooed, to highlight the importance of the subject, in the museological processes, through self-knowledge, self-esteem and self-criticism, in which the subject is at the same time a museological object, considered as a work of art. Then the tattooed subject then shares many of the problems that are also common to the Sociomuseological universe: he is the subject and object of memory and forgetfulness - mapping his territory; he is also a subject of power, of his body; it is a point of heritage identification through its aesthetics; it is the search for an identity or a difference in its territory, and it is the result of the phenomenological processes of modernity. These are just some of the points that will be discussed in this text.Key words: Sociomuseology; Identity; Power; Artistic Expression; Postmodernity